1999
DOI: 10.1007/bf02702350
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for massive black holes in the centers of active galaxies

Abstract: Naturally occurring water vapor maser emission at 1.35 cm wavelength provides an accurate probe for the study of accretion disks around highly compact objects, thought to be black holes, in the centers of active galaxies. Because of the exceptionally fine angular resolution, 200 microarcseconds, obtainable with very long baseline interferometry, accompanied by high spectral resolution, < 0.1 km s −1 , the dynamics and structures of these disks can be probed with exceptional clarity. The data on the galaxy NGC … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 55 publications
2
48
0
Order By: Relevance
“…One can also speculate on the possible existence of an edge-on molecular gas disk rotating around a super massive object by analogy with other megamasers (Moran et al 1999). Such a hypothesis is supported by the nature of the observed spectrum of the H 2 O maser towards NGC 6240 and its similarity to that of the so-called disk masers.…”
Section: What Is the Maser In Ngc 6240?mentioning
confidence: 79%
See 2 more Smart Citations
“…One can also speculate on the possible existence of an edge-on molecular gas disk rotating around a super massive object by analogy with other megamasers (Moran et al 1999). Such a hypothesis is supported by the nature of the observed spectrum of the H 2 O maser towards NGC 6240 and its similarity to that of the so-called disk masers.…”
Section: What Is the Maser In Ngc 6240?mentioning
confidence: 79%
“…Moran et al 1999). The detection rates of new masers remain quite low, less than ∼7% (e.g., Braatz et al 1996;Braatz et al 1997;Greenhill et al 1997).…”
Section: Or a Nuclearmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that the column density N H of N1, measured by X-ray observations, is at least a factor of several higher than that of N2 (Komossa et al 2003) and that the maser in N1 could be more enhanced through the thicker dust layer in our line of sight, amplifying the background radio source of N1. Also, the non-detection of the maser except for the compact continuum nucleus is consistent with the presence of a background nuclear continuum source being necessary to excite H 2 O megamasers that are associated with AGN activity (e.g., Moran et al 1999). On the other hand, the X-ray measurements of NGC 6240 revealed that both nuclei show the Compton-thick properties (Matt et al 2000), meaning each of them could host an obscured AGN.…”
Section: Nuclear Maser In Agnmentioning
confidence: 90%
“…Since the Braatz et al (1996Braatz et al ( , 1997 survey, eight more megamasers have been discovered 2 , bringing the current total to 24 (see the list in Moran, Greenhill, & Herrnstein 1999, plus Mrk 348 (Falcke et al 2000b) and NGC 6240 (Hagiwara, Diamond, & Miyoshi 2002;Nakai, Sato, & Yamauchi 2002)). All of the sources are in galaxies classified as either Sy 2 (14/24) or LINERs (10/24).…”
Section: Extragalactic Sourcesmentioning
confidence: 99%